EFEKTIVITAS KOMUNIKASI PEMBELAJARAN DARING SISWA SEKOLAH DASAR DI DESA BINTANG MERSADA KECAMATAN SIDIKALANG DI MASA PANDEMI COVID-19 - Dewi Sriwahyuni Sitepu; Anang Anas Azhar; Zuhriah (JIPDAS (Jurnal Ilmiah Pendidikan Dasar), 2022)
This study aims to determine the effectiveness of communication and the obstacles faced during the implementation of the online learning process. This study uses a qualitative method. The informant used was one teacher and seven students from a State Elementary School by purposive sampling. Data collection techniques used are interviews, observation, and documentation. The results of the study show that online learning communication during the pandemic is still not effective. This is indicated by the many obstacles faced both from the school and from the students that hinder the communication process such as inadequate facilities, internet quotas, weak networks, and lack of support from students' parents while online learning is implemented.